Hydroponic Vegetable Marketing Strategy in Pekanbaru: An Empirical Research - Yusnidar YUSNIDAR; Muhammad Adrian AGUSTA (International Journal of Environmental, Sustainability, and Social Science, 2024)
This study aims to analyze the marketing strategies applied in hydroponic vegetable businesses in Pekanbaru. The research method used is a qualitative descriptive method with a case study approach on several hydroponic business actors in the region. Data was collected through observation, interviews, and documentation. The results of the study indicate that effective marketing strategies for hydroponic vegetables in Pekanbaru include the 4P marketing mix approach (Product, Price, Promotion, and Place). The most effective strategy is to utilize social media as the main marketing tool, with a focus on product quality, competitive prices, educational promotions, and wide distribution through collaboration with various parties. This study recommends that hydroponic business actors continue to improve product innovation, optimize digital marketing, and quality service to increase sales.